2007
DOI: 10.1124/mol.107.035840
|View full text |Cite
|
Sign up to set email alerts
|

APETx1 from Sea Anemone Anthopleura elegantissima Is a Gating Modifier Peptide Toxin of the Human Ether-a-go-go- Related Potassium Channel

Abstract: We studied the mechanism of action and the binding site of APETx1, a peptide toxin purified from sea anemone, on the human ether-a-go-go-related gene (hERG) channel. Similar to the effects of gating modifier toxins (hanatoxin and SGTx) on the voltage-gated potassium (Kv) 2.1 channel, APETx1 shifts the voltage-dependence of hERG activation in the positive direction and suppresses its current amplitudes elicited by strong depolarizing pulses that maximally activate the channels. The APETx1 binding site is distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 54 publications
11
65
4
Order By: Relevance
“…To quantify the effect of Kv4.3 mutations on interaction with HpTx2, we determined the K d value for WT Kv4.3 and several of the Kv4.3 S3b mutants at toxin concentrations between 1 nM and 10 M HpTx2. We used a method previously used with the gatingmodifier toxins HaTx, Scodra griseipes toxin (SGTx), and APETx1 (Lee et al, 2003;Zhang et al, 2007). Like HpTx2, these toxins all interact with the S3b region of a voltagegated K ϩ channel; Kv2.1 in the case of HaTx and SGTx, Kv11.1 (human ether-à -go-go-related gene) with APETx1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the effect of Kv4.3 mutations on interaction with HpTx2, we determined the K d value for WT Kv4.3 and several of the Kv4.3 S3b mutants at toxin concentrations between 1 nM and 10 M HpTx2. We used a method previously used with the gatingmodifier toxins HaTx, Scodra griseipes toxin (SGTx), and APETx1 (Lee et al, 2003;Zhang et al, 2007). Like HpTx2, these toxins all interact with the S3b region of a voltagegated K ϩ channel; Kv2.1 in the case of HaTx and SGTx, Kv11.1 (human ether-à -go-go-related gene) with APETx1.…”
Section: Resultsmentioning
confidence: 99%
“…In several cases, careful channel mutagenesis studies have been performed. These studies have shown that the toxin binding sites are often complex and are dependent on either a combination of charged and hydrophobic amino acids or charge interactions alone (Swartz and MacKinnon, 1997b;Alabi et al, 2007;Catterall et al, 2007;Smith and Blumenthal, 2007;Swartz, 2007;Zhang et al, 2007;Bosmans et al, 2008;Norton and McDonough, 2008). HpTx2 is thus far unique among the ICK toxins in relying solely on hydrophobic contacts for channel interaction.…”
Section: Discussionmentioning
confidence: 99%
“…These toxins share a structural homology with the basic pancreatic trypsin inhibitor (BPTI), a very potent Kunitz-type protease inhibitor, and dendrotoxins (from mamba snakes) which are highly potent blockers of K V channels [10,11]. The third type is composed of toxins containing 41 or 42 amino acid residues and three disulfide bridges: BDS I and II toxins (A. viridis) inhibit K V 3.1, K V 3.2 and K V 3.4 currents by acting as channel-gating modulators and APETx1 (A. elegantissima) is a gating modifier toxin of K V 10.1 and K V 11.1 [12,13]. The type 4 family is represented by two putative homologous K V channel blocking peptides, SHTX I and II, from Stichodactyla haddoni [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the tarantula toxins JZTX-I and III bind to both Nav (see above) and Kv channels [134,145,146,149], ProTx-I interacts with Nav, Kv, and Cav channels, and ProTx-II interacts with Nav and Cav channels [148]. In addition, there are other unrelated toxins like sea-anemone toxins that affect Kv channels with a similar mechanism [151][152][153]. The amphipathic structure of the cysteine-knot toxins with a cluster of hydrophobic residues surrounded by polar residues [133] suggests that they are likely to partition into the membrane and possibly act on the VSD from there [64,[154][155][156][157].…”
Section: Toxinsmentioning
confidence: 99%